2015
DOI: 10.1007/s11136-015-0970-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Elderly Low Vision Quality of Life Questionnaire for less-developed areas of China

Abstract: A patient-derived ELVQoL Questionnaire was developed specifically for elderly, uneducated, rural Chinese. All the psychometric properties met accepted levels for a disease-specific Qol Questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…2) Option sorting analysis showed that the curve peak of 0, 1, 2, 3 scores were separated from each other and in the same order, indicating the four-point Likert response rating scale was reasonable-a phenomenon also reported in the validation of other vision scales [31][32] . The most useful classification of asthenopia in clinical practice is also four-point (non, mild, moderate and severe asthenopia) [1] , which was consistent with the score of each symptom and helpful for the classification according to the score.…”
Section: Discussionmentioning
confidence: 85%
“…2) Option sorting analysis showed that the curve peak of 0, 1, 2, 3 scores were separated from each other and in the same order, indicating the four-point Likert response rating scale was reasonable-a phenomenon also reported in the validation of other vision scales [31][32] . The most useful classification of asthenopia in clinical practice is also four-point (non, mild, moderate and severe asthenopia) [1] , which was consistent with the score of each symptom and helpful for the classification according to the score.…”
Section: Discussionmentioning
confidence: 85%
“…The study used the convenience sampling which cannot represent all population with visual impairment. The questionnaire interview is based on the ELVQoL [17], so does not include the specific needs such as education for children. Despite these limitations, this study is among the first to investigate the needs for visual improvement of patients with visual impairment in China.…”
Section: Discussionmentioning
confidence: 99%
“…Visual needs were the visual functions that patients really wanted to improve. Several questionnaires were used in the clinic according to different patients such as Elderly Low Vision Quality of Life Questionnaire (ELVQoL) [17], Low Vision Quality of Life Questionnaire, and Visual Function-25, of which ELVQoL was the most commonly used. Children less than 10 years old were accompanied by guardians and they answered questions together.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation